Usaha mengekalkan permainan tradisional Melayu Johor Kajian Kes : permainan Gasing tradisi di Kampung Parit Baru, Ayer Baloi, Pontian, Johor - Ishak, I. (Universiti Malaysia Sarawak, UNIMAS, 2007)
Top-spinning is one of the traditional games often played in Johor. This games is not only played before by adults but children as well. This research on traditional top spinning at Kampung Parit Baru, Ayer Baloi, Pontian aim to look at the role council of Pontian District and the residents of Kampung Parit Baru, Ayer Baloi, Pontian is preserving this traditional game that is slowly being forgotten especially by the malay youth in Johor